Algebraic diagrammatic construction schemes employing the intermediate state formalism: theory, capabilities, and interpretation - Dreuw, Andreas; Papapostolou, Antonia; Dempwolff, Adrian (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2023)
Algebraic diagrammatic construction (ADC) schemes represent a family of ab initio methods for the calculation of excited electronic states and electron-detached and -attached states. All ADC methods have been demonstrated to possess great potential for molecular applications, e.g., for the calculation of absorption or photoelectron spectra or electron attachment processes. ADC originates from Green’s function or propagator theory; however, most recent ADC developments heavily rely on the intermediate state representation or effective Liouvillian formalisms, which comprise new ADC methods and computational schemes for high-order properties. The different approaches for the calculation of excitation energies, ionization potentials, and electron affinities are intimately related, and they provide a coherent description of these quantities at equivalent levels of theory and with comparable errors. Most quantum chemical program packages contain ADC methods; however, the most complete ADC suite of methods can be found in the recent release of Q-Chem.
Online veröffentlicht: 27. Juli 2023
Gesehen am 25.09.2023